First language influences on multilingual lexicons - Booth, Paul; Clenton, Jon (Routledge, 2020)
"This collection brings together recent research on the influences between first and additional languages with a focus on the development of multilingual lexicons. Featuring work from an international group of scholars, the volume examines the complex dynamics underpinning vocabulary in second and third languages and the role first languages play within this process. The book is organized around three different facets of research in this area - lexical recognition, processing, and knowledge; the effects of first languages on second language reading and writing, collocations, and translation skills; and, vocabulary testing - drawing on examples from a variety of languages, including European languages, Arabic, and Japanese. Setting the stage for further research on the interplay between first languages and multilingual lexicons, this volume is key reading for students and researchers in applied linguistics, language learning and teaching, bilingualism, second language acquisition, and translation studies"--
Description based on print version record
Keywords: Second language acquisition / Case studies; Interference (Linguistics); Mentales Lexikon; Zweisprachigkeit; Fremdsprachenlernen; Übersetzung; Interferenz -- Linguistik; Aufsatzsammlung